Um estudo sobre os diferentes valores modais do verbo 'poder' em entrevistas jornalísticas do espanhol - Rinaldi, Natália [UNESP] (2015)
This work aims at describing the modal verb poder in Spanish journalistic interviews from the discursive, semantic and syntactic features that involve the verb, in order to verify how epistemic value differs from non-epistemic values. The modality classification adopted was proposed by Hengeveld (2004) and it is the basis for the treatment of modalities within the theoretical model of Functional Discourse Grammar (FDG), functional theory whose architecture follows a top-down operation, i.e. it starts with the speaker's intention and then works down to articulation. The accomplishment of this research, which was realized from a synchronic perspective, seeks to answer the follow questions: i) Which non-epistemic values can poder express in Spanish? ii) Is it possible to considerate poder as an auxiliary verb from the theory of Grammaticalization? iii) Does the construction of poder + infinitive that shows the highest level of grammaticalization correspond to epistemic values or non-epistemic values? iv) What is the relation between the layers in Representational Level and semantic values of epistemic modality and non-epistemic modalities expressed by poder? v) What is the contribution of the context to distinguish epistemic values from non-epistemic values expressed by poder in Spanish? To analyze contextual elements that distinguish from others when epistemic modality is expressed in comparison with non-epistemic modalities, some parameters were chosen, such as presence and features [human] and [animate] of the subject, type of States-of-Affair (SoA), grammatical person of the subject, as well as verbal tense and verbal mode and presence of negation before the modal verb. The corpus of this research consists of 20 journalistic interviews published in the Spanish magazine El País, selected randomly between the years 2000 and 2001, and it belongs to the corpus organized by Gasparini-Bastos (2004). The analysis allows verifying that the ...